Barriers in health seeking behaviour among tribal pregnant women in a hilly tribal area of Kashmir: a qualitative study - Zahoor, Nazia; Bashir, Khalid; Kausar, Zeenat; Ain, Syed Najmul (International Journal of Research in Medical Sciences, 2020)
Background: Maternal health is of paramount concern all over the world and has been a priority in India as well with the maternal health programs evolving over the time, addressing new arenas and overcoming challenges to reach the Maternal mortality ratio (MMR) target with quality. (1) In tribal areas various barriers in health seeking behavior are impediments towards maternal health. Methods: An explorative qualitative study was undertaken in a tribal area of Srinagar, Kashmir, which is a rural field practice area of the Department of Community Medicine Government Medical College, Srinagar. Focus group discussion (FGD) and in-depth interviews were conducted. Thematic analysis was used to analyze the FGD and in-depth interview data. Results: The data analysis generated following five themes: Theme 1: Perceptions and practices among tribal pregnant women in Faqir Gujree area. Theme 2: Socio-cultural influences, attitude and beliefs. Theme 3: Health system related barriers. Theme 4: Community related barriers. Theme 5: Cultural barriers among the pregnant women. Conclusions: There is a need of continuous behaviour change communication (BCC) with pregnant women and community members. In addition to addressing these issues, the health system related issues need to be addressed and improved in order to improve access to health care facilities by these pregnant women. Thus, a comprehensive tribal-sensitive health care system incorporating the above cultural issues is required to improve the health care access among these vulnerable ANC patients.